Medial Patellofemoral Ligament Reconstruction in a Below-Knee Amputee - Sherif El-Tawil; Marian Elfons Tawafig; Jonathan Miles (Case Reports in Orthopedics)
Patellar instability is a common finding in patients with below-knee amputation and yet management options are not commonly described in the literature. We describe the first reported case of a medial patellofemoral ligament reconstruction using allograft in a patient with a below-knee amputation. Clinical outcome at two-year follow-up remains very good.